Distributed interactive simulation - Machado, José Manuel (1997)
One's work aims at a context based, computing environment for Distributed Interactive Simulation (DIS), that uses the blackboard data model for message passing among processors, and was implemented using the SICStus Prolog language and the LINDA library of predicates. It allows for access via Internet and WWW forms; it accesses relational databases under Linux or Windows NT SQL servers; it enables the use of learning techniques from past experiences, cases and previous justification of situations; it manages the allocation of tasks to processors in an efficient way; and it accepts user interaction from Windows or Linux workstations. It also addresses the semantic structure of the communications, how the contextual cooperation between agents is made, how the user questions are interpreted and answered through a computer desk and how data and information are processed. The use of such an environment to simulate an inventory control system is considered.